Analisis Pendapatan Usahatani “Stevia” Di Desa Tountimomor Kecamatan Kakas Barat Kabupaten Minahasa - Rasuh, Indah Firgina; Kaunang, Rine; Pangemanan, Lyndon Reinhard Jacob (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the income and feasibility of Stevia farming in Tountimomor Village, West Kakas District, Minahasa Regency. The research was carried out for 3 months, from May to July 2022. The respondents in the study were determined deliberately. The data used are primary data collected through interviews based on questionnaires and secondary data obtained through Google Scholar in the form of books. The results showed that in the first 6 months the revenue did not cover all the costs incurred by farmers for the production of Stevia because all costs were incurred for 1 planting period which was for 6 years, so the income was still negative. Therefore, the second stage was continued, namely financial analysis to determine the feasibility of Stevia farming using the criteria of NPV, IRR, Net B/C and BEP. The results of the analysis of the feasibility of farming are feasible or Stevia farming in Tountimomor Village, West Kakas District, Minahasa Regency is feasible to implement.